Synthesis and pharmacological evaluation of novel substituted 9-deazaxanthines as A(2B) receptor antagonists - Isabel Nieto, MI (2010)
A new series of 9-deazaxanthine derivatives with various substituents at the heterocyclic system were synthesized and evaluated for their binding affinities for the four human recombinant adenosine receptors, A(1)-A(3) subtypes. A number of the 9-deazaxanthines derivatives 3a-m showed moderate-to-high affinity for hA(2B) receptors, with compound 3f showing a 32-fold selectivity for A(2B) over A(1) and a 2750-fold selectivity for A(2B) over A(2A).